ANALYSIS OF THE EFFECT OF WEATHER CONDITIONS AND CONVERSATIONS ON DRIVER SITUATION AWARENESS USING THE SITUATION AWARENESS RATING TECHNIQUE (SART) METHOD - Romadoni, Muhammad Ilham; Suryadi, Akmal (LPPM Universitas Trunojoyo Madura, 2024)
Driving is an activity of controlling vehicles on the road, either using motorcycles or cars that can pose a risk of accidents, the factors that cause accidents include human factors, vehicle factors, and environmental factors. The purpose of this study was to determine the effect of weather conditions and conversation on the situation awareness of car drivers (driving simulator) using the Situation Awareness Rating Technique (SART) method. The research subjects are Industrial Engineering students of UPN